Cerapanorpa, a new genus of Panorpidae (Insecta: Mecoptera) with descriptions of three new species - Gao, Chao; Hua, Bao-Zhen (Zootaxa, 2016)
A new genus of Panorpidae (Mecoptera), Cerapanorpa gen. nov., is erected with Panorpa obtusa Cheng, 1949 as its type species. The new genus can be readily recognized by having a single digitate anal horn on the posterior edge of tergum VI in males, and a broad main plate bearing two pairs of basal plates at the genital plate and a well-developed elongate axis in females. Nineteen described species are transferred from Panorpa Linnaeus, 1758 to the new genus. In addition, three new species, Cerapanorpa liupanshana sp. nov., Cerapanorpa protrudens sp. nov. and Cerapanorpa sinuata sp. nov. are described and illustrated. Panorpa alticola Zhou, 2000 syn. nov. is regarded as a junior synonym of P. obtusa Cheng, 1949. A key to genera of Panorpidae is updated to include the new genus. A key to species of Cerapanorpa is also presented.